Digital Marketing Adoption: Insights from Small and Medium Street Food Vendors - Ani Rakhmanita; Yasir Maulana; Mirza Abdi Khairusy (Widya Cipta: Jurnal Sekretari dan Manajemen, 2026)
Our study reveals the resource constraint faced by small and medium sized street food vendors in adopting digital marketing and explores how street food vendors address challenges. Data were collected through semi structured interviews with 20 street food vendors, then analyzed using qualitative analysis. This study reveals their readiness to adopt digital marketing, the benefits gained from digital marketing, and the challenges in taking digital marketing to next level. The diffusion of innovation theory is used as a theoretical lens that will help researchers understand this phenomenon. This theory attempts to predict the behavior of individuals and social groups in the process of innovation adoption, by considering four characteristic of innovation, such as relative advantage, compatibility, complexity, and trial. Discussion of these findings leads to insight for academics, culinary SMEs, and policy makers in developing relevant policies to economy